Neo-Colonialism and the Poverty of 'Development' in Africa - Langan, Mark (Contemporary African Political Economy, 2018)
This monograph reclaims neo-colonialism as an analytical force for making sense of poverty and the failure of 'development' strategies within many African states in an era of free market globalisation. Eschewing polemics and weaving three country case studies throughout each chapter (Ghana, Uganda and Zambia), the book offers a rigorous assessment of the origins of 'neo-colonialism' as a Marxian concept; provides an examination of two main varieties of neo-colonial intervention in the Africa state and highlights the complicity of certain African elites in perpetuating neo-colonial relations; examines some of the policy outcomes of both varieties of neo-colonialism; and last but not least examines the broader social and environmental consequences of neo-colonialism. The book provides an original contribution to studies of African political economy, demonstrating the on-going relevance of the concept of neo-colonialism, and reclaiming it for scholarly analysis in a global era.